Cycling power optimization system using link models of lower limbs with cleat-shaped biaxial load cells - Matsuda, A.; Yamashita, K.; Ishikura, K.; Takagi, H. (Procedia Engineering, 2014)
A new optimization system of cycling power was investigated in this paper. The developed system consisted of a newly designed biaxial load cells and analytical system using mechanical model of lower limb. The new biaxial load cells which were made by stainless steel (SUS304) were attached to the bottom of cycling-shoes instead of the plastic cleats. Cyclists are able to connect their cycling-shoes to pedals by the developed load cells. The sizes of load cells were almost same as plastic cleats (Shimano Corp) and measure the magnitude and direction of right and left pedal force using 16-strain gages, respectively. The analytical system solves the link model of human limbs to identify the positions and angles of each segment of lower limbs. The lower limbs model consisted of 3 segments, thigh, shank and foot. All position of every lower limb segments, joint torques and forces were calculated by this system. Additionally, the relationships between ankle angle and crank angle were also modelled by image-analysis software (TEMA 3D) with the high-speed camera (Photron FASTCAM SA4). This cycling power optimization system were applied to the amateur and expert cyclists to investigate applicability of our system.